2017
DOI: 10.1016/j.bbi.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Clk1 deficiency promotes neuroinflammation and subsequent dopaminergic cell death through regulation of microglial metabolic reprogramming

Abstract: Clock (Clk)1/COQ7 is a mitochondrial hydroxylase that is necessary for the biosynthesis of ubiquinone (coenzyme Q or UQ). Here, we investigate the role of Clk1 in neuroinflammation and consequentially dopaminergic (DA) neuron survival. Reduced expression of Clk1 in microglia enhanced the LPS-induced proinflammatory response and promoted aerobic glycolysis. Inhibition of glycolysis abolished Clk1 deficiency-induced hypersensitivity to the inflammatory stimulation. Mechanistic studies demonstrated that mTOR/HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
(52 reference statements)
2
39
0
Order By: Relevance
“…Both responses require rapid energy production which is produced when microglia undergo the metabolic switch to glycolysis . Glycolysis allows energy production and uptake of essential nutrients to support the rapid changes required by “activated” microglia in response to a stimulus, such as phagocytosis, proliferation, migration, and induction of protein synthesis for cytokine and chemokine secretion . Indeed, we identified the ability of the TREM2 variant expressing iPS‐Mg to undergo a normal switch in metabolism from a homeostatic, surveillance profile supported by oxidative phosphorylation, to one in which glycolysis is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Both responses require rapid energy production which is produced when microglia undergo the metabolic switch to glycolysis . Glycolysis allows energy production and uptake of essential nutrients to support the rapid changes required by “activated” microglia in response to a stimulus, such as phagocytosis, proliferation, migration, and induction of protein synthesis for cytokine and chemokine secretion . Indeed, we identified the ability of the TREM2 variant expressing iPS‐Mg to undergo a normal switch in metabolism from a homeostatic, surveillance profile supported by oxidative phosphorylation, to one in which glycolysis is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that Clk1 was involved in metabolic reprogramming in microglia cells (Gu et al . ). Thus, we next addressed whether Clk1 alters the glycolytic metabolism in glioma cells and how the metabolic reprogramming affects its role in the chemosensitivity of GL261 glioma cells.…”
Section: Resultsmentioning
confidence: 97%
“…; Gu et al . ). This study showed that knockdown of Clk1 results in the up‐regulation of HIF‐1α and inhibition of HIF‐1α expression reversed Clk1 deficiency‐triggered aerobic glycolysis and chemoresistance of glioma cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the results from our previous metabolomics analysis, there was a change in glycometabolism that oxidative phosphorylation shifted to aerobic glycolysis in CdTe@ZnS QD‐activated BV2 cells, which was observed in this study by the increased glycolysis level and glycolysis ability as well as the decreased ATP production. This glycolytic shift has been reported to depend on the activation of mTOR through a dectin‐1‐Akt‐HIF‐1α pathway (Cheng et al, ; Gu et al, ). Herein, the activation of mTOR and AKT as well as mTOR and HIF‐α were observed in the hippocampus and BV2 cells treated with CdTe/ZnS QDs, respectively, and the pretreatment with mTOR inhibitor rapamycin effectively inhibited the glycolytic shift.…”
Section: Discussionmentioning
confidence: 96%